The effects of antioxidants on knee osteoarthritis: A systematic review and meta-analysis - Nejadhosseinian, Mohammad; Djalalinia, Shirin; Haerian, Hoda; Alikhani, Majid; Mansour, Asieh; Mousavian, Amir-Hossein; Mardani-Fard, Heydar Ali; Kasaeian, Amir; Faezi, Seyedeh Tahereh (Frontiers in Nutrition, 2022)
Objective Knee osteoarthritis (KOA) is one of the growing health problems with a considerable burden. With recent research on the possible effectiveness of antioxidants in the remission of KOA symptoms, a systematic review and meta-analysis was required to confirm this hypothesis. Design Literature studies were searched on the most comprehensive databases such as PubMed, International Scientific Indexing, and Scopus, with no language and time restrictions. On 17 July 2021, a search strategy was developed based on the roots of “osteoarthritis (OA)” and “antioxidants,” with no time or language limitations. As the primary outcome, pain was evaluated based on all indicators for evaluating pain [e.g., Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain scores, the visual analog scale (VAS), and the numerical rating scale (NRS)]. The symptoms and functions of KOA and quality of life (QOL) were also considered as secondary outcomes, each of which was measured and reported by the corresponding instrument in the studies. To measure the changes in pain, symptoms, and functions of participants, we included randomized controlled trials with a placebo control or other medical therapeutic interventions. Publication bias was assessed using Begg's funnel plot and Egger's regression test, which was deemed to be statistically significant at 0.1, and the results were checked by the trim-and-fill test. Results After refinement, data were extracted from 31 documents from 7,698 primary searched papers. Using the VAS as a reliable psychometric measuring instrument, the present study revealed that a significant difference in the characteristics of disease-related symptoms of patients with KOA was reached after antioxidant therapy (standardized mean difference (SMD): 0.467, 95% confidence interval (CI): 0.303–0.632, p < 0.0001). The results reported by WOMAC confirmed no significant difference in the combined score, difficulty score, pain score, and stiffness score. Conclusion As the first comprehensive systematic review of the association between antioxidant supplementation and KOA, this study showed that antioxidants can decrease disease-related symptoms in patients with KOA. The results can be useful for health policy decisions and future related studies. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022351060, identifier: CRD42022351060.